# Thread: can't work out particular integral of this second order ODE, or figure how to rewrite

1. ## can't work out particular integral of this second order ODE, or figure how to rewrite

a) determine a particular integral of the second order differential equation u'' + Bu' +u = sin(wt)

in the form u(t) = Csin(wt) + Dcos(wt) where C and D are functions of w that should be found explicitly.

b) rewrite u(t) in the form u(t) = Asin(wt + y) where A is the amplitude of the long term response and y is a phase lag between the driving force and the response. show that A = sqrt(C^2 + D^2) and hence that

A = 1/ (sqrt(((1-w^2)^2) + (B^2)(w^2))

2. Originally Posted by thatgirlrocks
a) determine a particular integral of the second order differential equation u'' + Bu' +u = sin(wt)

in the form u(t) = Csin(wt) + Dcos(wt) where C and D are functions of w that should be found explicitly.
A linear system forced with a sinusoidal forcing function has a steady state sinusoidal reaponse. So for the particular integral take trial solution:

$u(t)=C \sin(\omega t) + D \cos(\omega t)$

Now plug this into the differential equation and on the left hand side collect together all the terms with $\sin(\omega t)$ and $\cos(\omega t)$. Equate the coefficient of the first of these to $1$ and of the second to $0$ and you will have a pair of simultaneous linear equations for $C$ and $D$ in terms of $\omega$ and $B$. Solve them and you are done.

(there is an implicit assumption that $\omega$ is not a resonance of the system, if it is a bit more case is required)

CB

3. $u'' + Bu' + u = \sin{\omega t}$.

Complementary solution:

$m^2 + Bm + 1 = 0$

$m = \frac{-B \pm \sqrt{B^2 - 4(1)(1)}}{2}$

$= \frac{-B \pm \sqrt{B^2 - 4}}{2}$.

Therefore

$u_c = C_1 e^{\frac{-B + \sqrt{B^2 - 4}}{2}} + C_2 e^{\frac{-B - \sqrt{B^2 - 4}}{2}}$.

Particular solution:

Guess

$u_p = C_3\sin{\omega t} + C_4\cos{\omega t}$

$u_p' = \omega C_3\cos{\omega t} - \omega C_4\sin{\omega t}$

$u_p'' = -\omega^2C_3\sin{\omega t} - \omega^2C_4\cos{\omega t}$.

Substituting into the DE...

$u'' + Bu' + u$

$= -\omega^2 C_3\sin{\omega t} - \omega^2 C_4\cos{\omega t} + B(\omega C_3\cos{\omega t} - \omega C_4\sin{\omega t}) + C_3\sin{\omega t} + C_4\cos{\omega t}$

$= (C_3 - B\omega C_4 - \omega^2C_3)\sin{\omega t} + (C_4 + B\omega C_3 -\omega^2C_4)\cos{\omega t}$.

Since this equals $\sin{\omega t}$, that means

$C_3 - B\omega C_4 - \omega^2C_3 = 1$ and $C_4 + B\omega C_3 -\omega^2C_4 = 0$.

Solve the equations simultaneously for $C_3$ and $C_4$.

$u = u_c + u_p$
$u = C_1 e^{\frac{-B + \sqrt{B^2 - 4}}{2}} + C_2 e^{\frac{-B - \sqrt{B^2 - 4}}{2}} + C_3\sin{\omega t} + C_4\cos{\omega t}$.
You will need to substitute $C_3$ and $C_4$.